Ethiopia's spatial and structural transformation: Public policy and drivers of change - Schmidt, Emily; Dorosh, Paul A.; Kedir Jemal, Mekamu; Smart, Jenny (International Food Policy Research Institute, 2018)
This paper evaluates Ethiopia’s urbanization trend during the last four decades, while also considering Ethiopia’s structural transformation and recent public investments to promote greater industrialization within the country. Ethiopia’s urban population grew 4.2 percent per year between 1994 and 2015, far outpacing the overall population growth rate of 2.5 percent. Compared to the urban growth rate of Africa (3.5 percent per year), Ethiopia experienced a 20 percent faster urban population growth rate (UNDESA 2015). Urbanization in Ethiopia is expected to reach 38 percent by 2050. However, this level is relatively low compared to the majority of sub-Saharan Africa (SSA) countries. Improved road infrastructure, rural to urban migration and secondary city development is increasing urbanization within the country. In addition, recent public investments to promote industrialization and increase manufacturing labor opportunities via newly constructed and planned industrial parks are projected to increase urbanization and bolster structural transformation across the country. We evaluate these investments and demographic trends within the context of other countries in sub-Saharan Africa, as well as with the experience of India and China. Ethiopia’s investment in higher-value manufacturing and service activities via economic zones may provide similar infrastructure to that of China and India’s ‘township and village enterprises’ (TVE). However, a focus on increasing human capacity and labor mobility will be necessary to ensure that rural farmers are able to take advantage of labor opportunities outside of the agriculture sector. We calculate the projected economic impact of Ethiopia’s planned industrial zones and sugar factories and find that while public and private investment in industrial and agro-industrial parks may provide a catalyst for future growth, they are likely to provide only a small share of total output and employment. Investments in sugar factories are anticipated to total USD 5.2 billion, with estimated production of USD 3.6 billion and value-added of USD 3.3 billion. However, an increase in sugar output of this magnitude would imply massive sugar exports that may not be financially profitable.